Four-armed Indra - Temples of India Project Team (Jio Institute, 2024)
Indra, the God of heaven, is depicted with four arms. In his upper right hand, he holds a vajra (thunderbolt), and in his upper left hand, an ankusha (goad). His lower right-hand makes a varada hasta (boon-giving gesture) and holds a rosary, while his lower left hand carries a kamandalu (water pot). Crowned, Indra is accompanied by his mount, the elephant.